Visual function in infants with antenatal Zika virus exposure - Zin, Andrea A. (J AAPOS, 2018)
PURPOSE: To report the findings of a cross-sectional study of visual function in infants with confirmed or suspected antenatal Zika virus (ZIKV) infection seen at a single referral center in Rio de Janeiro. METHODS: Infants were examined following the ZIKV outbreak period at Fernandes Figueira Institute/FIOCRUZ. Visual function was considered abnormal if an infant could not fix and follow a standardized high-contrast target (10 cm) by 3–6 months of age. Visual function and associations with structural eye abnormalities, central nervous system (CNS) abnormalities, microcephaly, and nystagmus were assessed. Sensitivity and specificity of screening criteria for structural eye abnormalities was assessed. RESULTS: A total of 173 infants met inclusion criteria. Reduced visual function was found in 52 infants (30.0%) and was significantly associated with eye abnormalities (40/52; OR = 44.2; 95% CI, 16.6–117.6), CNS abnormalities (50/52; OR = 64.0; 95% CI, 14.7–277.6), microcephaly (44/52; OR = 31.5; 95% CI,12.7–77.8), and nystagmus (26/52; OR = 120.0; 95% CI, 15.6–924.5). Using microcephaly as screening criteria for the detection of eye abnormalities provided a sensitivity of 88.9% (95% CI,76.0–96.3) and specificity of 82.8% (95% CI, 75.1–88.9). Using both abnormal visual function and microcephaly increased sensitivity to 100% (95% CI, 92.1–100.0) and decreased specificity to 80.5% (95% CI, 72.5–86.9). CONCLUSIONS: Infants with suspected antenatal ZIKV infection and reduced visual function should be referred to an ophthalmologist. Visual function assessments are helpful in screening for antenatal ZIKV exposure in resource-limited settings and can identify infants who may benefit from visual habilitation.